2007
DOI: 10.1002/ejic.200600715
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest Complexes of Oligopyridine Cryptands: Prediction of Ion Selectivity by Quantum Chemical Calculations

Abstract: The structures and complex‐formation energies for the cryptands 6,6′,6″,6″′,6″″,6″″′‐bis[nitrilotri(methylene)]tris(2,2′‐bipyridine) (1) and 2,2′,2″,9,9′,9″‐bis[nitrilotri(methylene)]tris(1,10‐phenanthroline) (2) with alkali and alkaline‐earth cations are obtained by PM3/SPASS and density functional (B3LYP/LANL2DZp) calculations and the results used to predict the ion selectivity. Both cryptands 1 and 2 have a cavity size similar to [2.2.2] and prefer Ca2+ and Sr2+, while 1 has a preference for K+ and 2 favour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…We recently demonstrated that reaction (4) is a valuable tool to determine ion selectivity as a function of the ionic radii [39] and to examine cavity size of the cryptands as a variable. [21,40] In agreement with the experimental kinetic data, the smaller cryptand binds Li + better and slows down its exchange rate (Table 2). On comparing the calculated Li-O and Li-N bond lengths of the three structures with the bond length in [Li(OH 2 ) 4 ] + and [Li(NH 3 ) 4 ] + , the trend can easily be understood (see Table 6 and Figure 11).…”
Section: Theoretical Calculationssupporting
confidence: 87%
“…We recently demonstrated that reaction (4) is a valuable tool to determine ion selectivity as a function of the ionic radii [39] and to examine cavity size of the cryptands as a variable. [21,40] In agreement with the experimental kinetic data, the smaller cryptand binds Li + better and slows down its exchange rate (Table 2). On comparing the calculated Li-O and Li-N bond lengths of the three structures with the bond length in [Li(OH 2 ) 4 ] + and [Li(NH 3 ) 4 ] + , the trend can easily be understood (see Table 6 and Figure 11).…”
Section: Theoretical Calculationssupporting
confidence: 87%
“…The sparkle concept was then applied to alkaline and alkaline earth complexes as well. 38,39 Subsequently, the model was extended to all other lanthanide ions within AM1, 4048 and was later parameterized for PM3 4955 and for PM6. 56 In 2006, we published an article in which we compared Sparkle calculations with ab initio effective core potential calculations.…”
mentioning
confidence: 99%
“…Among quantum chemical methods for computational modelling of macrocyclic ligands and their complexes, DFT has been successfully applied to the calculation of the thermodynamic parameters for the cryptate formation reaction [26][27][28]. Since hydrogen atoms usually have low X-ray scattering factors and, as a result, their coordinates are not generally determined, structures from crystal data were subject to proton optimisation at the B3LYP/6-31G Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…The first one is to consider the bare metal according to scheme (1) and this is the most popular [26]. The second considers a solvated metal cluster, such as hexa-aqua metal complex [M(H2O) 6 ] 2+ , instead of the bare metal [27]. The third approach combines the first two [28], wherein the first step is the desolvation of the metal ion according to 9 scheme (11) and the second is the bare metal reaction with the cryptand as in scheme (1).…”
mentioning
confidence: 99%